PERBANDINGAN HASIL BELAJAR MENGGUNAKAN MODEL PEMBELAJARAN TPS DAN TPT SMAN 1 PALLANGA KABUPATEN GOWA - Abudzar Ghifari; Andi Maulana; Thamrin Tayeb (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2017)
This thesis discusses cooperative learning model that Think Pair Share and The Power of Two on the subject of the Digestive System Student Class XI SMAN 1 Pallangga. With the aim of research to find out whether there are differences in learning outcomes of students who are taught by koopertaif learning model Think Pair Share and The Power of Two on the subject of the digestive system of class XI student of SMAN 1 Pallangga. This research is experimental form of Quasi Experimental Design (quasi-experimental) design study is a